Pengaruh Employee Engagement terhadap Burnout dengan Happiness at Work Sebagai Variabel Moderasi dalam Perspektif Manajemen Insani - Mimi Fitriani; Weny Rosilawati; Ridwansyah Ridwansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The many tasks and authorities make KPPS officers stressed. This study aims to see whether happiness at work will affect the stress level of KPPS officers. The method in this study is a quantitative method with the help of SPSS software. Based on the results of the data analysis, it is stated that the significance value of the interaction variable between Employee Engagement and burnout moderated by Happiness at work is 0.000 (> 0.05), so it is concluded that the happiness at work variable (M) is able to moderate the effect of employee engagement on the burnout variable, which means that if KPPS employees in West Teluk Betung have positive emotions at work, then KPPS employees will have a positive work environment and will not experience burnout or stress at work.